Domestic demand for agricultural products in Costa Rica: a case study for eight products - Kreijns, M.S. (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
45 pág, 1 ilus, 30 tab, 23 ref. También como: Field Report - Atlantic Zone Programme (CATIE-AUW-MAG) no. 118